2011
DOI: 10.1590/s0100-67622011000600004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de macronutrientes sobre o crescimento e qualidade de mudas de canafístula cultivadas em Latossolo Vermelho-Amarelo distrófico

Abstract: RESUMO -Peltophorum dubium (canafístula, angico-cangalha, angico-amarelo) é uma espécie de rápido crescimento, rusticidade e ótima para uso em reflorestamentos mistos de áreas degradadas. Devido à carência de informações sobre a nutrição dessa espécie, o objetivo deste trabalho foi avaliar o efeito de doses de N, P, K, Ca, Mg e S sobre crescimento, produção de biomassa e índices EFFECT OF MACRONUTRIENTS ON THE GROWTH AND QUALITY OF Peltophorum dubium SEEDLINGS GROWN IN DYSTROPHYCOUS RED YELLOW LATOSOIL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…The Dickson quality index of seedlings for plants submitted to different phosphorus doses ( Figure 2) also showed linear growth for D. nigra seedlings, and since the highest DQI value produces the best quality seedlings, the dose of 500 mg kg -1 presented the best results in this case. Cruz et al (2011) also found increasing DQI values in canafistula (Peltophorum dubium) seedlings. The best results however, were found for the dose of 600 mg kg -1 of phosphorus for Dystrophic Red Latosol/typic haplustox soil.…”
Section: /10mentioning
confidence: 75%
“…The Dickson quality index of seedlings for plants submitted to different phosphorus doses ( Figure 2) also showed linear growth for D. nigra seedlings, and since the highest DQI value produces the best quality seedlings, the dose of 500 mg kg -1 presented the best results in this case. Cruz et al (2011) also found increasing DQI values in canafistula (Peltophorum dubium) seedlings. The best results however, were found for the dose of 600 mg kg -1 of phosphorus for Dystrophic Red Latosol/typic haplustox soil.…”
Section: /10mentioning
confidence: 75%
“…Isso porque, o suprimento inadequado de um nutriente mineral resulta em distúrbio nutricional que se manifesta por sintomas de deficiência característicos, sendo que tais distúrbios podem estar relacionados às funções desempenhadas pelos nutrientes no metabolismo da planta (TAIZ;ZEIGER, 2004). Desta forma, a nutrição mineral é um fator importante da fisiologia das árvores, uma vez que o suprimento adequado de nutrientes é essencial para o sucesso do crescimento das espécies nativas, sendo isso confirmado por Cruz et al (2011) cujo trabalho mostra que a aplicação de fertilizantes contendo N, P, K, Ca, Mg e S possibilitou significativo aumento do crescimento das mudas de canafístula (Peltophorum dubium (Spreng.) Taub.…”
unclassified